Incidence and management of the main serious adverse events reported after COVID‐19 vaccination - Teresa Padilla‐Flores; Alicia Sampieri; Luis Vaca (Wiley, 2024)
Abstract Coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2n first appeared in Wuhan, China in 2019. Soon after, it was declared a pandemic by the World Health Organization. The health crisis imposed by a new virus and its rapid spread worldwide prompted the fast development of vaccines. For the first time in human history, two vaccines based on recombinant genetic material technology were approved for human use. These mRNA vaccines were applied in massive immunization programs around the world, followed by other vaccines based on more traditional approaches. Even though all vaccines were tested in clinical trials prior to their general administration, serious adverse events, usually of very low incidence, were mostly identified after application of millions of doses. Establishing a direct correlation (the cause‐effect paradigm) between vaccination and the appearance of adverse effects has proven challenging. This review focuses on the main adverse effects observed after vaccination, including anaphylaxis, myocarditis, vaccine‐induced thrombotic thrombocytopenia, Guillain-Barré syndrome, and transverse myelitis reported in the context of COVID‐19 vaccination. We highlight the symptoms, laboratory tests required for an adequate diagnosis, and briefly outline the recommended treatments for these adverse effects. The aim of this work is to increase awareness among healthcare personnel about the serious adverse events that may arise post‐vaccination. Regardless of the ongoing discussion about the safety of COVID‐19 vaccination, these adverse effects must be identified promptly and treated effectively to reduce the risk of complications.